Rural credit, food security, and resilience: An empirical evaluation from Kenya - Ndegwa, Michael K.; Ward, Patrick S.; Shee, Apurba; You, Liangzhi (International Food Policy Research Institute, 2025)
In this paper, we examine the role of credit in enhancing rural households’ food security and resilience. In so doing, we consider resilience as a higher order capacity outcome, different from traditional development outcomes associated with households’ or individuals’ welfare. We evaluate the effectiveness of two types of agricultural production credit products, one a traditional credit and one that is linked to rainfall index insurance to protect borrowers against the adverse effects of drought. Based on a randomized controlled trial conducted in Machakos county, Kenya, we report both intent-to-treat effects as well as local average treatment effects to demonstrate the impacts of these credit products not only among borrowers, but the broader effects of expanding rural credit markets. We see generally low levels of food security resilience among our sampled households, but we find compelling evidence that credit and expanded credit markets more broadly had beneficial impacts on enhancing households’ food security and resilience. Despite the differences in the two credit products being evaluated, we do not find an appreciable difference in the effects of the two credit types, concluding that the expansion of affordable agricultural credit markets should be among the key policy tools for building resilience among rural smallholders.